(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article explores the development of creative abilities among students pursuing technical specialties in higher education. It highlights the importance of creativity as a critical component in engineering and technological innovation. The study analyzes modern pedagogical strategies, including project-based learning, interdisciplinary collaboration, and digital tools, that contribute to fostering students’ creative thinking. The article also discusses international practices and the integration of creativity into technical curricula to prepare students for complex problem-solving in real-world contexts.